Total flavonoids from sea buckthorn ameliorates lipopolysaccharide/cigarette smoke‐induced airway inflammation. (17th June 2019) - Ren, Qing‐cuo; Li, Xuan‐hao; Li, Qiu‐yue; Yang, Hai‐ling; Wang, Hong‐ling; Zhang, Hai; Zhao, Lin; Jiang‐yong, Si‐lang; Meng, Xian‐li; Zhang, Yi; Shen, Xiao‐fei
Abstract : The total flavonoids from sea buckthorn (TFSB) exhibit a potent anti‐inflammatory activity; however, the effect of TFSB on respiratory inflammatory disease is not fully known. The present study evaluated the potential of TFSB to prevent airway inflammation and the underlying mechanism. The results showed that TFSB remarkably inhibited lipopolysaccharide/cigarette smoke extract (LPS/CSE)‐induced expression of IL‐1β, IL‐6, CXCL1, and MUC5AC at both mRNA and protein levels in HBE16 bronchial epithelial cells. TFSB also decreased the production of PGE2 through inhibition the expression of COX2 in LPS/CSE‐stimulated HBE16 cells. Furthermore, bronchoalveolar fluid and histological analyses revealed that LPS/cigarette smoke exposure‐induced elevated cell numbers of neutrophils and macrophages in bronchoalveolar fluid, inflammatory cell infiltration, and airway remodeling were remarkably attenuated by TFSB in mice. Immunohistochemical results also confirmed that TFSB decreased the expression of IL‐1β, IL‐6, COX2, CXCL1, and MUC5AC in LPS/CS‐exposed mice. Mechanistically, TFSB blocked LPS/CSE‐induced activation of ERK, Akt, and PKCα. Molecular docking further confirmed that the main components in TFSB including quercetin and isorhamnetin showed potent binding affinities to MAPK1 and PIK3CG, two upstream kinases of ERK and Akt, respectively. In summary, TFSB exerts a potent protective effect against LPS/CS‐induced airway inflammation through inhibition of ERK, PI3K/Akt, and PKCα pathways, suggesting that TFSB may be a novel therapeutic agent for respiratory diseases.